STRUCTURE AND PRINCIPLES OF MONITORING THE QUALITY OF VOCATIONAL EDUCATION IN BLENDED LEARNING (Innovative professional education, 2024)
The subsection describes the approaches to defining the essence and structure of monitoring the quality of education, provides a list of regulatory documents on themechanisms for preparing and conducting monitoring of the quality of education and educational activities in educational institutions, and provides a justification for theprinciples of organising monitoring of the quality of education in the context of vocational education in a blended learning environment.
Keywords: monitoring, quality of education, monitoring of the quality of education, professional education, blended learning